Consumers’ Awareness on Their Basic Rights and Willingness to Pay for Organic Vegetables in Ethiopia - Belay Tizazu Mengistie (Publisher of Widyagama University of Malang (UWG Press), 2020)
In developing countries, widely reported incidents of dangerous levels of pesticides in food have stimulated the demand for organic food, a movement to choose organic agriculture. It also makes more people have desires to consume chemical free foods. This study, therefore, assessed the consumers’ awareness of their eight basic rights and willingness to pay for organic vegetables in Ethiopia. The data were collected from 200 respondents (consumers) from Addis Ababa and 80 smallholder vegetable farmers at Ziway and Meki through a combination of random and purposive sampling procedures using a structured interview and were analyzed using descriptive analysis. The results show that vegetable producers used a lot of chemicals, but not in a safe way or at the optimum level. The findings also show that the overall degree of consumers’ awareness on the eight consumer rights is low. Furthermore, willingness to pay premium prices about 5-50% to obtain organic products, which can be viewed as the cost of investment in human health, is encouraging. There is a need to target agricultural policies relating to handling practices and for public health policies to be more differentiated in promoting food safety. Informing consumers about unique characteristics of organic production methods, the strict inspection and required third party certification might be a promising strategy to develop the market for organic vegetables in Ethiopian urban centers. JEL Classification: D18, Q10, Q18